ACCEPTANCE OF NEW MAKSA ADVENTURE COMMUNITY MEMBERS USING THE PROFILE MATCHING METHOD - Muhammad Arif Saputra; Deni Juhana; After Valent Duarisah; Shobari Irawan; Hafni Mahligai Ramadhani; Nur Khoerudin (Universitas Teknokrat Indonesia, 2023)
Acceptance and selection of new members of the Organization is something that needs to be determined according to quality. In terms of determining prospective new members, a lot of consideration is needed and it is difficult to determine who will be elected. Acceptance of members is a routine activity carried out by the organization, including the Maksa Adventure community. Profile matching itself is a decision-making mechanism with the assumption that there are ideal predictor variables that must be owned by applicants, not the minimum level that must be met or passed. To carry out the process of selecting the best Members by using the profile matching method which can assist the Organization in solving the problems it faces and getting the right decision. From the several steps that have been implemented using the profile matching method, the result is the right decision and as expected, namely the management can select the best members who will later become permanent members of Maksa Adventure. The steps in carrying out decision support using the profile matching method are first to assess the criteria for the Maksa Adventure community, then by determining the range and weight of the criteria obtained, after obtaining the conditional value, then look for the standard competency value, then you can look for the gap value by looking at the provisions of the available weighting table. , then determine the core factors such as interviews, equipment, experience by means of NC/IC and second factors such as public speaking by means of NS/IS, after obtaining determine the calculation of the total value by means of (x)% NCF +(x)% NSF, then do ranking to determine the best value to support a decision, this ranking process is a continuation step of the process of calculating the total value, because in this study only used four criteria in processing the data, and did not use other criteria, the ranking percentage calculation was not carried out by looking at the results of the total value that has been calculated before. The Decision Support System for Admission and Selection of Members of Organizations can be used as a guideline for organizations in handling the process of accepting new members. In the acceptance stage of the Journal of Acceptance of New Members of the Maksa Adventure Community with a Total Member Value of 1 obtained at 4.8.Keyword:organization, profile matching, core factor, secondary factor, decision support system.